Separation of cis- and trans-Asarone from Acorus tatarinowii by Preparative Gas Chromatography - H. L. Zuo; F. Q. Yang; X. M. Zhang; Z. N. Xia (Journal of Analytical Methods in Chemistry)
A preparative gas chromatography (pGC) method was developed for the separation of isomers (cis- and trans-asarone) from essential oil of Acorus tatarinowii. The oil was primarily fractionated by silica gel chromatography using different ratios of petroleum ether and ethyl acetate as gradient elution solvents. And then the fraction that contains mixture of the isomers was further separated by pGC. The compounds were separated on a stainless steel column packed with 10% OV-101 (3 m × 6 mm, i.d.), and then the effluent was split into two gas flows. One percent of the effluent passed to the flame ionization detector (FID) for detection and the remaining 99% was directed to the fraction collector. Two isomers were collected after 90 single injections (5 uL) with the yield of 178 mg and 82 mg, respectively. Furthermore, the structures of the obtained compounds were identified as cis- and trans-asarone by 1H- and 13C-NMR spectra, respectively.